2020
DOI: 10.1021/acs.analchem.0c00370
|View full text |Cite
|
Sign up to set email alerts
|

Nondestructive High-Sensitivity Detections of Metallic Lithium Deposited on a Battery Anode Using Muonic X-rays

Abstract: Metallic Li deposited on the anode is known to induce short circuiting and degradation of the charge capacity of Li-ion batteries. However, no reliable technique is currently available to observe such Li metal without removing the case of the battery. An elemental analysis using muonic X-rays is proposed here because of its unique properties of nondestructive measurement, high sensitivity to light elements, and depth resolution. We demonstrated that this technique can be applied to detection of Li deposited on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 39 publications
(61 reference statements)
0
22
0
Order By: Relevance
“…Their merits include being nondestructive and sensitive to light elements and depth analysis, and they have been used to detect Li in Li-ion batteries. 41 Cells are the basic structural and functional units of living organisms. Owing to the heterogeneity and diversity of individual cells, single-cell analysis is of great importance.…”
Section: The Analytical Advances In Metallomicsmentioning
confidence: 99%
“…Their merits include being nondestructive and sensitive to light elements and depth analysis, and they have been used to detect Li in Li-ion batteries. 41 Cells are the basic structural and functional units of living organisms. Owing to the heterogeneity and diversity of individual cells, single-cell analysis is of great importance.…”
Section: The Analytical Advances In Metallomicsmentioning
confidence: 99%
“…[15][16][17] used Muon Induced X-ray Emission (MIXE), while the Ref. [18] used Muonic Atom X-ray Spectroscopy (MAXRS); all of which describe the same technique), a non-destructive technique, which was developed more than 40 years ago [14,[19][20][21], has recently been used extensively with pulsed muon beams for elemental analysis [16,18,[22][23][24][25][26][27][28][29][30][31][32][33][34]. The advantage of this technique is that it is able to probe deep into the material, up to a few millimeters, and does not lead to a severe radiation damage of the sample.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive research has been conducted to clarify the properties of the electrode/electrolyte interface, including composition, morphology, mechanical properties, and atomiclevel structure. [1][2][3][4][5][6][7][8][9][10][11][12][13] It has been reported that the thickness of the SEI is about 20 nm and its main components are Li compounds including constituent elements of the electrolyte, such as LiF, LiOH, and Li 2 CO 3 . [14][15][16][17][18] In addition, Sacci et al reported that SEI is about twice as dense as the electrolyte on the basis of the results of in situ electrochemical scanning transmission electron microscopy (ec-S/TEM).…”
Section: Introductionmentioning
confidence: 99%